CRISPR/Cas9‐based knockout reveals that the clock gene timeless is indispensable for regulating circadian behavioral rhythms in Bombyx mori. (18th September 2020) - Nartey, Moses Addo; Sun, Xia; Qin, Sheng; Hou, Cheng‐Xiang; Li, Mu‐Wang
Abstract: Circadian rhythms, which are ubiquitous and adaptive, occur across all species, from microbes to humans, in which they organize and modify behavior and physiology. timeless ( tim ) is a canonical clock gene. The core composition of the Drosophila melanogaster endogenous circadian clock has been extensively investigated; however, in lepidopteran insects, including Bombyx mori, the mechanism is complicated and little is known regarding the participation of tim in the negative feedback loop responsible for behavioral activities. To arrive at a comprehensive understanding of the role of tim in the B. mori endogenous circadian clock, we exploited the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 gene editing system. We attempted to elucidate the functions of tim in the circadian clock of B. mori using Bmtim mutants. The knockouts affected two circadian behavioral activities: adult emergence and embryo hatching rhythms. Quantitative real‐time polymerase chain reaction results confirmed that tim‐ knockouts induced relative reductions in the expression levels, and thereby the oscillation amplitudes, of Bmper and Bmclk messenger RNAs during both the photophase and scotophase. Additionally, the daily rhythmic expression of Bmdbt was upregulated in the photophase and downregulated in the scotophase in a tim‐ knockout. Our study reveals that tim is integral to the B. mori circadian clock and may be involved in regulating eclosion and hatching rhythms. Abstract : Circadian rhythms, which are ubiquitous and adaptive, occur across all species, from microbes to humans, in which they organize and modify behavior and physiology. timeless ( tim ) is a canonical clock gene. The core composition of the Drosophila melanogaster endogenous circadian clock has been extensively investigated; however, in lepidopteran insects, including Bombyx mori, the mechanism is complicated and little is known regarding the participation of tim in the negative feedback loop responsible for behavioral activities. To arrive at a comprehensive understanding of the role of tim in the B. mori endogenous circadian clock, we exploited the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 gene editing system.